Acquisition of life skills and its influence on the career maturity of university student judo players - Yamamoto, K.; Shimamoto, K. (Japan Journal of Physical Education, Health and Sport Sciences, 2019)
In order to provide effective career education support for university athletes, it is necessary to accumulate fundamental knowledge about their acquisition of life skills. Therefore, the purpose of this study was to examine the influence of life skills on career maturity as a judo player in university student judo players. In June 2016, a survey of 510 university judo players (male: 408, female: 102, mean age: 19.70 ± 1.28years, mean period of experience: 12.37 ± 5.70years) was conducted using the Appraisal Scale of Required Life Skills for College Student Athletes (Shimamoto et al., 2013). This scale evaluates the life skills required by athletes using 10 dimensions (stress management, setting goals, thinking carefully, appreciating others, communicating, maintaining etiquette and manners, always making one`s best effort, taking responsibility for one`s own behavior, being humble, and maintaining physical health and well-being). In addition, the Life Career Maturity Scale (Sakayanagi, 1999) was used to evaluate the students` life career interest, autonomy, and planning ability. An analysis focusing on the students` sex and the presence or absence of experienced registration of certified athletes in the All Japan Judo Federation was also conducted. First, factor analysis was conducted to classify the life skills into 4 aspects "self-control skills", "goal achievement skills", "communication skills", and "problem solving skills" and it was shown that reliability and validity were generally satisfactory. Next, the influence of life skills on the 4 aspects on carrier maturity was examined by structural equation modeling. This showed that goal achievement skills had a significant positive influence on both male and female career maturity. Similarly, self-control skills and goal achievement skills had a significant positive influence on career maturity in common with the presence or absence of having been registered as a certified athlete in the All Japan Judo Federation. Based on the above results, it was suggested that acquisition of self-control skills and goal achievement skills is necessary to raise the level of career maturity in university student judo players. Therefore, it is considered important to offer educational support for university students judo players using acquisition of both these skills.